Study and validation on mitochondrial and immune-related hub genes in gestational diabetes mellitus based on bioinformatics - Zhao, Xin; Ma, Yuehan; Sun, Jianbin; Zhang, Xiaomei (Frontiers in Endocrinology, 2025)
BackgroundMitochondria and immune function play pivotal roles in the pathogenesis of gestational diabetes mellitus (GDM). However, the intricate molecular mechanisms underlying their involvement remain elusive. Therefore, this study aimed to elucidate the interaction between mitochondria-related genes (MRGs) and immune-related genes (IRGs) in GDM.MethodsIn this study, GDM-related datasets (GSE103552, GSE154414, and GSE173193) were integrated along with MRGs and IRGs. Differential expression analysis was conducted on GSE103552 to identify differentially expressed genes (DEGs), which were then intersected with MRGs and IRGs. Correlations among the intersection genes were evaluated, and those with statistical significance and strong correlation were selected as candidate genes. Three machine learning algorithms were subsequently applied to further refine the selection of signature genes. The optimal model was determined, and genes within this model were designated as signature genes. Expression levels of these genes were then examined, and those showing significant differences and consistent trends between GDM and control groups in both GSE103552 and GSE154414 datasets were identified as hub genes. Further analyses included chromosomal and subcellular localization, enrichment, regulatory mechanism, and drug prediction analyses of hub genes. Key cell types were analyzed in GSE173193. Finally, the expression of hub genes was validated by reverse transcription quantitative polymerase chain reaction (RT-qPCR).ResultsComprehensive analysis identified MRPL15, MRPL22, and MRPS18C emerged as pivotal hub genes, each showing significantly lower expression levels in the GDM group. Chromosomal localization revealed MRPS18C on chromosome 4, MRPL22 on chromosome 5, and MRPL15 on chromosome 8. Subcellular distribution analysis indicated that MRPL15 and MRPL22 were predominantly localized in the nucleus, whereas MRPS18C was mainly cytoplasmic. Enrichment analysis showed that spliceosome, proteasome, Parkinson disease, and ribosome pathways were enriched by the hub genes. Regulatory analysis revealed that YY1 regulated MRPS18C and MRPL22, ARID3A regulated MRPS18C and MRPL15, and FOXC1 regulated MRPL22 and MRPL15. Finally, results of RT-qPCR results confirmed that MRPL15, MRPL22, and MRPS18C were significantly downregulated in the GDM group.ConclusionOur findings highlight the significance of MRPL15, MRPL22, MRPS18C, monocytes, and villous cytotrophoblast cells in GDM. These insights provide valuable implications for the diagnosis and potential therapeutic interventions targeting of GDM.